Global, regional and local health impacts of civil aviation emissions. (26th February 2015) - Yim, Steve H L; Lee, Gideon L; Lee, In Hwan; Allroggen, Florian; Ashok, Akshay; Caiazzo, Fabio; Eastham, Sebastian D; Malina, Robert; Barrett, Steven R H
Abstract: Aviation emissions impact surface air quality at multiple scales—from near-airport pollution peaks associated with airport landing and take off (LTO) emissions, to intercontinental pollution attributable to aircraft cruise emissions. Previous studies have quantified aviation's air quality impacts around a specific airport, in a specific region, or at the global scale. However, no study has assessed the air quality and human health impacts of aviation, capturing effects on all aforementioned scales. This study uses a multi-scale modeling approach to quantify and monetize the air quality impact of civil aviation emissions, approximating effects of aircraft plume dynamics-related local dispersion (∼1 km), near-airport dispersion (∼10 km), regional (∼1000 km) and global (∼10 000 km) scale chemistry and transport. We use concentration-response functions to estimate premature deaths due to population exposure to aviation-attributable PM2.5 and ozone, finding that aviation emissions cause ∼16 000 (90% CI: 8300–24 000) premature deaths per year. Of these, LTO emissions contribute a quarter. Our estimate shows that premature deaths due to long-term exposure to aviation-attributable PM2.5 and O3 lead to costs of ∼21 bn per year. We compare these costs to other societal costs of aviation and find that they are on the same order of magnitude as global aviation-attributable climate costs, and one order of magnitude larger than aviation-attributable accident and noise costs.